Non-discrimination in international trade in services : 'likeness' in WTO/GATS - Diebold, Nicolas F. (Cambridge, UK : Cambridge University Press, 2010)
'The principle of non-discrimination is fundamental to the regulation of international trade in goods and services. In the context of trade in goods, the concept of'like products' has become a key element of the legal analysis of whether a trade obstacle violates GATT non-discrimination obligations. The equivalent concept of'like services and service suppliers' in GATS rules on non-discrimination has received little attention in WTO jurisprudence. In light of the remaining uncertainties, Nicolas Diebold analyses the legal problems of the GATS'like services and services suppliers' concept using a contextual and comparative methodology. The'likeness' element is not analysed in isolation, but in context with'less favourable treatment' and regulatory purpose as additional elements of non-discrimination. The book also explores how far theories from non-discrimination rules in GATT, NAFTA, BITs and EC as well as market definition theories from competition law may be applied to'likeness' in GATS'--Provided by publisher.
Includes bibliographical references and index.
Keywords: General Agreement on Trade in Services -- (1994); Service industries -- Government policy; Trade regulation